Method construction of pad foundation / Nur Naimie Nadjwa Khairuddin - Khairuddin, Nur Naimie Nadjwa (Universiti Teknologi MARA, Perak, 2018)
A concrete pad foundation is the simplest and cost-effective footing used for the vertical support and the transfer of building loads to the ground. The pad foundation also one of the types of the Foundation in the construction. This pad foundation one of the part of the substructure. This reported conducted for the process to construct the pad foundation for pavilion. The objective for this report are to discuss the process involved to construct the pad foundation and to identify the important and problem facing during construct the pad foundation. Only one building has been construct to its superstructure is Surau but the others only for its substructure. In this report it focusing on Pavilion's pad foundation. The main findings for this report is the process involved to construct the pad foundation in this Kompleks Sukan Rembau.